THE ELECTROCHEMICAL PULSEWISE METHOD FOR MONITORING OF CORROSION AND MECHANICAL DAMAGE - A. G. Arkhypov; O. V. Lyubimova-Zinchenko; D. A. Kovalyov (Приборы и методы измерений)
The electrochemical pulsewise method for corrosion and mechanical damage monitoring the process equipment operated in liquid electrolyte agent is provided. The developed method makes it possible to inspect the equipment condition either according to the formation rate of disturb pulses which are recorded during a certain period of time or according to the equipment potential behave our in time.